![49(2a - 3b)^2 - 16(a + 2b)^2 49(2a - 3b)^2 - 16(a + 2b)^2](https://tex.z-dn.net/?f=49%282a+-+3b%29%5E2+-+16%28a+%2B+2b%29%5E2)
explain please.
Answers
Answered by
1
Step-by-step explanation:
49(2a - 3b)^2 - 16(a + 2b)^2
= 49( 4a^2 - 12ab + 9b^2 ) - 16( a^2 + 4ab + 4b^2 )
= (196 - 16)a^2 - (588 + 64)ab + (441 - 64)b^2
= 180a^2 - 652ab + 377b^2
Similar questions
Math,
6 hours ago
Computer Science,
6 hours ago
Environmental Sciences,
11 hours ago
Science,
8 months ago
Math,
8 months ago
Math,
8 months ago